Monoclonal Antibodies Against EGFR, HER2, and VEGF: Mechanistic Insights and Emerging Strategies in Targeted Cancer Therapy - Ananda Kumar Chettupalli; Paramvir Singh Tomar; Shikha Yadav; Chandan Mondal (Current Drug Therapy, 2026)
Introduction: Monoclonal antibodies (mAbs) that target receptor-mediated oncogenic pathways have revolutionized oncology research. Better therapeutic indices are possible with these mAbs for targeted tumor treatment. This review covers receptor-targeted monoclonal antibodies targeting the EGFR, HER2, and VEGF pathways in solid tumors, as well as their therapeutic use and development. Methods: The study searched the scientific literature to identify key FDA-authorized studies on the EGFR, HER2, and VEGF/VEGFR pathways, as well as translational research and mechanistic investigations of these pathways. The focus was on developing next-generation antibody engineering platforms, understanding resistance mechanisms, and using biomarkers to select patients. Results: Therapeutic monoclonal antibodies (mAbs) inhibited carcinogenic signaling pathways, such as RAS/MAPK and PI3K/AKT. When mAbs engage with the immune system, they activate the complement system and induce antibody-dependent cellular cytotoxicity. Clinical trials have shown that biomarker-selected cohorts of patients with colorectal, breast, lung, gastric, and other cancers have improved survival rates without disease recurrence. Mutations, activation of alternative pathways, and changes in the tumor microenvironment may generate intrinsic and acquired resistance, reducing long-term efficacy. Discussion: Resistance patterns highlight the need for adaptable strategies that account for the biology of multiple target organisms. Cell-penetrating platforms, glycoengineering, antibody-drug conjugates, and bispecific antibodies have been developed to improve therapeutic efficacy, decrease escape mechanisms, and increase drug accessibility. Conclusion: Receptor-targeting monoclonal antibodies are crucial in precision oncology. Future advances must include molecular profiling, smart combination approaches, and nextgeneration antibody engineering to improve response durability and patient outcomes.